Monoterpanes as molecular indicators to diagnose depositional environments for source rocks of crude oils and condensates - Wang, Guangli; Cheng, B.; Wang, T.; Simoneit, B.; Shi, S.; Wang, P. (Pergamon, 2014)
A total of 74 crude oils and condensates originating from various deposits were collected in Tarim, Junggar, Beibuwan and Bohai Bay basins and analyzed by comprehensive two dimensional gas chromatography–time of flight mass spectrometry (GC × GC–TOFMS) in order to investigate the occurrence and distributions of C9 and C10 hydrocarbons. 3-Ethyl-2-methylheptane and 1,1,2,3-tetramethylcyclohexane, two C10 compounds possibly derived from monoterpenoids via cracking and reduction, may be formed under anoxic conditions during diagenesis. We suggest that the ratio of 3-ethyl-2-methylheptane to 3-methylnonane (MT1) coupled with the ratio of 1,1,2,3-tetramethylcyclohexane to propylcyclohexane (MT2), are useful parameters to infer depositional environments and to distinguish oil families. The oils and condensates formed from source rocks deposited under anoxic conditions show high 3-ethyl-2-methylheptane and 1,1,2,3-tetramethylcyclohexane levels (both MT1 and MT2 > 0.5). Whereas, the hydrocarbons derived from source rocks deposited in oxic conditions contain low amounts of 3-ethyl-2-methylheptane and 1,1,2,3-tetramethylcyclohexane (both MT1 and MT2 < 0.5). These monoterpane parameters may be useful in petroleum exploration, especially for light oils and condensates where most high molecular weight biomarkers could be cracked or eliminated through fractionation.